2010
DOI: 10.1029/2009ja015128
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosheath for almost‐aligned solar wind magnetic field and flow vectors: Wind observations across the dawnside magnetosheath at X = −12 Re

Abstract: [1] While there are many approximations describing the flow of the solar wind past the magnetosphere in the magnetosheath, the case of perfectly aligned (parallel or antiparallel) interplanetary magnetic field (IMF) and solar wind flow vectors can be treated exactly in a magnetohydrodynamic (MHD) approach. In this work we examine a case of nearly-opposed (to within 15°) interplanetary field and flow vectors, which occurred on October 24-25, 2001 during passage of the last interplanetary coronal mass ejection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 34 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…But KHI is still likely to be generated under IMFs greatly deviating from the due north orientation. Farrugia et al [] reported Wind observation of the equatorial boundary layer at dawn possibly presented with the KHI at the inner edge of LLBL under almost aligned solar wind magnetic field and flow vectors. Most recently, Tang et al [] find the KHI can still be excited at both flanks of magnetopause under the radial IMF with a global MHD simulation.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…But KHI is still likely to be generated under IMFs greatly deviating from the due north orientation. Farrugia et al [] reported Wind observation of the equatorial boundary layer at dawn possibly presented with the KHI at the inner edge of LLBL under almost aligned solar wind magnetic field and flow vectors. Most recently, Tang et al [] find the KHI can still be excited at both flanks of magnetopause under the radial IMF with a global MHD simulation.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…[] and Farrugia et al . [], the Petrinec‐Russell'96 model was used by Dušík et al . [], and the approximation of Fairfield and models by Sibeck et al'91 and Shue et al'97 were used by Farrugia et al .…”
Section: Models and Magnetopause Standoff Distance Approximationsmentioning
confidence: 99%
“…The foreshock pressure variations cause transient magnetopause motion [Sibeck et al, 1989]. Various aspects of the transient magnetopause motion at the dayside and flanks under radial IMF were comprehensively studied in many papers [e.g., Labelle et al, 1990;Sibeck and Newell, 1995;Laakso et al, 1998;Sibeck et al, 2000;Merka et al, 2003;Shue et al, 2009;Farrugia et al, 2010;Suvorova et al, 2010;Korotova et al, 2011;Turner et al, 2011]. Generally, the amplitude of transient motion ranges from 0.5 to 2 R E that is within 20% of nominal subsolar magnetopause or 10% of the flank magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…Shue et al [2009] investigated a case with multiple THEMIS spacecraft wherein the magnetopause was found to rebound, with fast sunward flows confined to a relatively small region of the magnetopause. Farrugia et al [2010] examined an interval when Wind was in the magnetosheath and ACE in the solar wind. The interplanetary flow was within 15° of the flow vector, and fair agreement was found with an analytic formulation of magnetic field components derived from perturbations to the Spreiter and Rizzi model (Spreiter and Rizzi [1974]).…”
mentioning
confidence: 99%